A Social Insecurity as Predictor: Dynamics of Senior Secondary School Students Achievements in Agricultural Science in Ekiti State - Ogunjobi, Pius Olanrewaju; Makinde, Veronica Ibitola; Fabamise , Deborah Bolanle (Journal of Applied And Theoretical Social Sciences, 2022)
This study sought to establish whether perceived insecurity of the school environment can predict the achievement of senior high school students in Agricultural Science in Ekiti State. It also sought to find out whether gender has any influence on perceived insecurity of school environment as a predictor of achievement in senior secondary school students in Agricultural Science Education. There are two research questions and null hypotheses which were formulated to serve as a guide to the study. The findings of this study showed that the Perceived Precariousness of the school surrounding significantly predicts senior secondary school students' achievement in agricultural science education while gender does not significantly influence the achievement of students in agricultural science in a perceived precariousness situation. The conclusion of the study was that secondary school students should be educated on the importance of perceived Precariousness in the school community as a predictor of their achievement in agricultural science education. It was recommended that strong awareness or orientation should be given to students on the significance of perceived Precariousness in the school community as a predictor of achievement in agricultural science.